2012
DOI: 10.1007/s10880-012-9346-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Its Relationship to Mental Health and Quality of Life in Adults with Cystic Fibrosis

Abstract: Research from the general population indicates an important role for self-esteem in mental health, but limited research in this area exists in the cystic fibrosis (CF) literature. This study aimed to explore the predictive value of self-esteem and health-related quality of life (HRQoL) in mental health symptoms in adults with CF. Seventy-four participants, recruited online, completed the Clinical Outcomes in Routine Evaluation-Outcome Measure 34 (CORE-OM), Rosenberg Self-esteem Scale and Cystic Fibrosis Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…5 Our findings are in line with this study and extend this association to measures of selfesteem, which is also compromised in CF. 30 These findings underline the importance of a high level of peak aerobic capacity as a contributor to psychological and sociological well-being. We found that both STS repetitions and 6MWD, even when expressed as a product of body weight, had only minor positive associations with HRQOL and self-esteem.…”
Section: Discussionmentioning
confidence: 82%
“…5 Our findings are in line with this study and extend this association to measures of selfesteem, which is also compromised in CF. 30 These findings underline the importance of a high level of peak aerobic capacity as a contributor to psychological and sociological well-being. We found that both STS repetitions and 6MWD, even when expressed as a product of body weight, had only minor positive associations with HRQOL and self-esteem.…”
Section: Discussionmentioning
confidence: 82%
“…Spiritual factors interestingly have been shown to contribute positively on treatment adherence in CF patients [193]. Social behavior factors such as self-esteem and social stigma can also be associated with pulmonary function in CF [194]. Studies have demonstrated the prevalence of anxiety and depression in patients with CF and their parents to be as high as 30%, significantly higher than in the general population [195, 196].…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to those of Standage and Gillison (2007), who found, through three different models of structural equations, that SE is able to predict health-related QL, that is, the QL positively predicted the overall SE, and that both are distinct but related variables. As far as it is known, these seem to be the quantitative indications that there is a bidirectionality in the relation between the QL and SE, given the predominance existent in the literature that treats SE as a predictor of the QL, without considering a possible feedback (Kuehner & Buerger, 2005;Novato et al, 2008;García-Martinez et al, 2012;Platten et al, 2013;Manhas, 2014;Joseph et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…SE is the individual own appraisal, which describes his/her positive and negative views (Freire & Tavares, 2011 (Lachman & Weaver, 1998); on the other hand, a lower SE regards unemployment, less integration with the community, impaired physical health, and a general decrease in functionality (Laferrier et al, 2015). The literature on the relations between SE and QL has been based on the study of self-esteem as a requirement, a predictive factor of better levels of quality of life (Kuehner & Buerger, 2005;Standage & Gillison, 2007;Novato, Grossi, & Kimura, 2008;García-Martinez, De Paz, & Márquez, 2012;Platten, Newman, & Quayle, 2013;Manhas, 2014;Joseph, Royse, Benitez, & Pekmezi, 2014).…”
Section: Introductionmentioning
confidence: 99%